Efektivitas KUP dalam Memulihkan Kerugian Pendapatan Negara Akibat Tindak Pidana Administratif Perpajakan - Muhammad Rizky Subardy; Ismansyah Ismansyah; Khairani Khairani (UNES Law Review, 2023)
Indonesian realization of state revenue from the taxation section is still not optimal and the ratio at just 84.44% (eighty-four point forty-four percent). So, it needed some efforts to optimize the tax revenue. One of the ways to Strengthen the tax administration law is by adding criminal law rules, hereinafter referred to as administrative penal law. Therefore, the principles of administrative penal law which carry out the concept of ultimum remedium has also applied to the General Taxation Law 2019 (KUP 2009). However, based on data from the Indonesia Directorate General of Taxes in 2020, the violators who use the ultimum remedium mechanism are only 5.56% (five-point fifty-six percent). Meanwhile, the fines paid by convicts are only 0.050% (zero point zero fifty percent) from all the criminal tax cases that are decided by the court. This certainly indicates, that there are problems that can not be resolved and be accommodated by the KUP 2009 in the form of optimizing the recovery of state losses due to administrative criminal acts in the taxation section. Based on the fact, that the state changed the KUP 2009 through the Omnibus Law and Harmonization of Tax Regulation Law, that be expected to be able to recover losses in the state revenue effectively.